The beneficial effects of square dance on musculoskeletal system in early postmenopausal Chinese women: a cross-sectional study - Jie Sun; Chen Yao; Ziping Wang; Jiancheng Wu; Bo Zhang; Zhenyu Zhou; Fan Liu; Yafeng Zhang (BMC, 2022)
Abstract Background This study was set to investigate the correlation between square dance and musculoskeletal system of early postmenopausal Chinese women. Methods Chinese postmenopausal women, who had been without menstruation for 1-10 years from the onset of menopause were recruited from community centers for this study. A standardized structured face-to-face interview was performed to collect demographic information, life styles, personal medical history, diet and menstrual status. Subjects who had been practicing regular square dance without participated in other sports activities for more than 2 years and over 4 h per week (usually more than 45 min per time and more than 5 times per week) were assigned to square dance group. Those postmenopausal women who had not participated in regular exercises (no more than 0.5 h per week) were recruited as the sedentary control group. Bone mineral density (BMD) of spine, total hip and femoral neck was measured by using dual-energy X-ray absorptiometry. Lower limb muscle strength was measured for the non-dominant leg, body flexibility was measured by a simple trunk bend-and-reach test, and body balance was evaluated using a single-stance test for the non-dominant leg. Independent two-tailed Student's t-test was used for data analysis. Results 152 subjects from community centers were selected for this study and divided into square dance group (n = 74) and control group (n = 78). The square dance subjects had higher lumbar spine BMD (p = 0.01) and total hip BMD (p = 0.02) than control subjects, but there was no significant difference of femoral neck BMD (p = 0.48) between these two groups. Functional testing indicated that square dance subjects had higher lower limb muscle strength (p < 0.01) and longer single-stance time (p = 0.02) than the control subjects, but there was no significant difference in trunk bend-and-reach (p = 0.12) between these two groups. Conclusion Our results show that postmenopausal Chinese women can get beneficial effects, like higher BMD, stronger lower limb muscle and improved body balance ability on musculoskeletal system by participating in square dance regularly.